Chylous ascites as a complication of intraabdominal Mycobacterium avium complex immune reconstitution inflammatory syndrome. Issue 3 (3rd July 2018) - Dean, Ryan K.; Subedi, Rogin; Karkee, Ashraya
ABSTRACT: Chylous ascites is an uncommon finding of triglyceride-rich lymph in the peritoneal cavity. There are a variety of reported etiologies for chylous ascites; however, the reporting of chylous ascites among AIDS/HIV-positive patients is quite uncommon. This finding as a complication of immune reconstitution inflammatory syndrome is even more unusual. Here we report a case of an HIV-positive man with a history of colonic Mycobacterium avium complex who developed chylous ascites in the setting of increasing CD4 counts and decreasing viral load, suggestive of immune reconstitution inflammatory syndrome.